Multiculturalism as a Socio-Historical Context of Intercultural Learning and Development of Intercultural Curriculum - Lungulov, Biljana S.; Gajić, Olivera Đ. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The paper analyses the phenomena of multiculturalism and interculturalism as social movements, as ubiquitous values, and significant and relatively progressive practices of contemporary society, and especially as an integral part of the curricula and outcomes of education policy. In that sense, the social context for the emergence and development of multiculturalism, i.e., its socio-historical genesis and key characteristics have been analysed. Also, popular debates, criticisms or challenges concerning this phenomenon and social and especially educational practice have been presented in the paper. The paper then emphasises the importance of a particular “reverse” from multiculturalism towards interculturalism, which is a much more fruitful approach related to the cultural diversity of society and the accompanying curricula and educational policies. Finally, the concept of intercultural learning, as a significant and courageous educational practice that relies on the stated values of multiculturalism and interculturalism in a given society, has been presented and critically analysed. Intercultural learning in education, as well as the lived experience, is conceptualised as an important and relatively transformative process that can lead to changes in behaviour, but also change the ways in which the stakeholders observe, interpret, and understand the world around them.